Safety and Efficacy of Anifrolumab in Systemic Lupus Erythematosus: Systematic Review with Network Meta-analysis - Fatima, Rawish; Aziz, Muhammad; Khader, Yasmin; Lee-Smith, Wade; Altorok, Nezam (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.